Determination of aldehydes and ketones in fuel ethanol by high-performance liquid chromatography with electrochemical detection - Saczk, A. A.; Okumura, L. L.; de Oliveira, M. F.; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Vieweg, 2006)
A new methodology was developed for analysis of aldehydes and ketones in fuel ethanol by high-performance liquid chromatography (HPLC) coupled to electrochemical detection. The electrochemical oxidation of 5-hydroxymetkylfurfural, 2-furfuraldehyde, butyraldehyde, acetone and methyl ethyl ketone derivatized with 2,4-dinitrophenylhydrazine (DNPH) at glassy carbon electrode present a well defined wave at +0.94 V; +0.99 V; +1.29 V; +1.15 V and +1.18 V, respectively which are the basis for its determination on electrochemical defector. The carbonyl compounds derivatized were separated by a reverse-phase column under isocratic conditions with a mobile phase containing a binary mixture of methanol /LiClO4(aq) at a concentration of 1.0 x 10(-3) mol L-1 (80:20 v/v) and a flow-rate of 1.1 mL min(-1). The optimum potential for the electrochemical detection of aldehydes-DNPH and ketones-DNPH was +1.0 V vs. Ag/AgCl. The analytical curve of aldehydes-DNPH and ketones-DNPH presented linearity over the range 5.0 to 400.0 ng mL(-1), with detection limits of 1.7 to 2.0 ng mL(-1) and quantification limits from 5.0 to 6.2 ng mL(-1), using injection volume of 20 mu L. The proposed methodology was simple, low time-consuming (15 min/analysis) and presented analytical recovery higher than 95%.
Keywords: column liquid chromatography; electrochemical detection; aldehydes and ketones in fuel ethanol; dinitrophenylhydrazones